GADD153 expression does not necessarily correlate with changes in culture behavior of hybridoma cells - Chartrand Kevin; Mallory Matthew; Gauthier Eric R (BMC Biotechnology, 2007)
Abstract Background The acute sensitivity of some hybridoma cell lines to culture-related stresses severely limits their productivity. Recent developments in the characterization of the stress signals modulating the cellular phenotype revealed that the pro-apoptotic transcription factor Gadd153 could be used as a marker to facilitate the optimization of mammalian cell cultures. In this report, we analyzed the expression of Gadd153 in Sp2/0-Ag14 murine hybridoma cells grown in stationary batch culture and subjected to two different culture optimization paradigms: L-glutamine supplementation and ectopic expression of Bcl-xL, an anti-apoptotic gene. Results The expression of Gadd153 was found to increase in Sp2/0-Ag14 cells in a manner which coincided with the decline in cell viability. L-glutamine supplementation prolonged Sp2/0-Ag14 cell survival and greatly suppressed Gadd153 expression both at the mRNA and protein level. However, Gadd153 levels remained low after L-glutamine supplementation even as cell viability declined. Bcl-xL overexpression also extended Sp2/0-Ag14 cell viability, initially delayed the induction of Gadd153, but did not prevent the increase in Gadd153 protein levels during the later phase of the culture, when cell viability was declining. Interestingly, L-glutamine supplementation prevented Gadd153 up-regulation in cells ectopically expressing Bcl-xL, but had no effect on cell viability. Conclusion This study highlights important limitations to the use of Gadd153 as an indicator of cell stress in hybridoma cells.